If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 11 = 6y + -13 Combine like terms: -2 + 11 = 9 9 = 6y + -13 Reorder the terms: 9 = -13 + 6y Solving 9 = -13 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 9 + -6y = -13 + 6y + -6y Combine like terms: 6y + -6y = 0 9 + -6y = -13 + 0 9 + -6y = -13 Add '-9' to each side of the equation. 9 + -9 + -6y = -13 + -9 Combine like terms: 9 + -9 = 0 0 + -6y = -13 + -9 -6y = -13 + -9 Combine like terms: -13 + -9 = -22 -6y = -22 Divide each side by '-6'. y = 3.666666667 Simplifying y = 3.666666667
| 3(6+y)=2x | | 7-7x=-10 | | ln(2x+14)=5 | | 4-8=4(x+7) | | (8+7i)(8-7i)= | | (X+Y)+(X-Y)=90 | | (c+x)+3(h+x)+(2m+c)-h= | | f=3+2x | | f=4+2x-1 | | x^2+0.5x+0.5=0 | | (X+4)4x(x+4)4x=38 | | 0.25=5+1 | | 7=25+5s | | k-4h= | | x+11=-12 | | 2b+2h=p | | 9-3c+8s= | | 6y+3=8y-7 | | 5h+6m+3l+f+(h+f)-2m= | | -2+2x=3+5x | | 5(2x-6)=-4 | | -3(6w-4s)= | | y-1=-3+9 | | 5h+6m+3l+f+(2m+c)-h= | | 7x-6y=-20 | | X+Y+X-Y=90 | | 8x+2=9x-4 | | (8x+3)=-4 | | 1n(6-2n)=99 | | 8x+2+9x-4=180 | | Y=0.25x^3-3x | | 5a-19=-74 |